Weak and Strong Time Consistency in Differential Oligopoly Games with Capital Accumulation - Roberto Cellini; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2005)
We illustrate two differential oligopoly games with capital accumulation where, alternatively, the accumulation dynamics of productive capacity is modelled either `a la Solow—Swan or `a la Ramsey. We show that in the first case the open-loop Nash equilibrium is only weakly time consistent, while in the second it is strongly so, although the Ramsey game is not state linear.
Keywords: 330; Oligopol; Zeitkonsistenz; Investition; Theorie